Análise dosimétrica em órgãos envolvidos no tratamento radioterápico da próstata - Maria Angelina Mendes (2019)
The procedure of quality control in radiotherapy treatments favors the estimation of the absorbed dose in organs that receive ionizing radiation as treatment. This method enhances existing treatment protocol quality procedures as well as reduces the risk of accidents. The physical simulators allow the evaluation and optimization of the dose absorbed in a radiotherapy treatment. The main objective of this study was to estimate the absorbed dose in the target and organs at risk of a prostate cancer treatment with the use of two different types of radiation detectors. From the calibration curves and the uncertainty value estimated in the calibration report of the linear accelerator of 6 MV, it was possible to assess the absorbed dose values in the detectors. The results were compared with two treatment planning and simulation software. The mean dose in the prostate reached the expected 95% and 99% of the total dose applied to the target with the two types of detectors. These values are within the range of -5% to + 7% on the uniform target dose distribution recommended by the ICRU Report No. 50. The analysis of the results was done in two distinct ways, by position having been consolidated by organs and extremities. Regarding the analysis positions, one of the detectors had a high average dose in relation to the other at almost all points, reaching up to 30% more of the maximum dose applied. In general, when analyzing the absorbed dose values found in the detectors as well as in the two planning software, there was good correlation, showing that there are differences in absorbed dose values in the two types of detectors that should be taken into account when used. The technique allowed estimating the dose distribution in irradiation of the male pelvis of the Alderson simulator in a treatment of 3D Conformational Radiotherapy.